Reduction of nestlings' vocalizations in response to parental alarm calls in the Southern House Wren, Troglodytes musculus - Serra, Catalina (2011)
Breeding birds often give alarm calls when a predator is near the nest. These calls have been proposed to serve as distraction displays for the predator, alerts for a mate conveying information about the presence of a threat, or a warning for nestlings about a potential risk. These functions, however, may not be mutually exclusive. In our study, we assessed if alarm calls uttered by breeding Southern House Wrens, Troglodytes musculus, are made to warn nestlings about risk. If so, we expected that nestlings would reduce overall activity in the nest and that the parents' call rate would be related to the detectability of the young (e. g., vocalizations). We experimentally elicited parents' alarm calls and compared nestling behavior before and after giving that stimulus. We found that Southern House Wren nestlings reduced their time spent vocalizing and remained inactive for longer when their parents called. Therefore, nestlings reduced their detectability by decreasing their activity inside the nest when their parents produced alarm calls. On the other hand, parental calling rates were not related to the nestling activity registered in any experimental stage. Therefore, we failed to find reliable results supporting the hypothesis that parent calling is uttered to silence nestlings. These results appear to indicate that alarm calling by breeding birds might fulfill other functions besides alerting nestlings. Future studies of this species are necessary to understand if parents are warning nestlings about a threat when they emit alarm calls.